Monitoring the Environmental, Social and Economic Dimensions of the Landing Obligation Policy - Christou, Maria; de Juan, Silvia; Vassilopoulou, Vassiliki; Stergiou, Konstantinos I.; Maynou, Francesc (Frontiers in Marine Science, 2019)
Aiming to end the practice of discarding unwanted catches back to the sea within European marine waters, an obligation to land the catches of all regulated commercial species was introduced with the Common Fisheries Policy by the first of January 2019. The implementation of this new fisheries regulation urges the definition of standard monitoring protocols to track potential changes in the fishery system. Importantly, this framework needs to be multi-dimensional to capture the ecological, social and economic components of the system. Aiming to address this challenge, a set of 39 candidate indicators were identified by means of literature review and expert consultation. Experts in European fisheries gathered to discuss the selection of a restricted set of indicators to understand changes in fishery systems resulting from the implementation of the landing obligation (LO). A survey was completed by the experts to assess the adequacy of the indicators against pre-defined quality criteria and to identify expected direction of change. Based on survey results, the 39 indicators were ranked according to their adequacy for the monitoring of the LO potential effects. This ranking was dominated by indicators related to the exploited species. Because the LO is not yet fully implemented, experts expressed uncertainty in the properties of many indicators, particularly of ecosystem and social indicators. The feasibility to operationalise a monitoring framework with the prioritised indicators was explored with data from a Spanish demersal otter-trawl fishery, an exercise that evidenced that most indicators could be collected and that it would be feasible to track these variables over time in the framework of a monitoring program.